Urban Ecosystem Study for the City of Bangkok during ASIA-AQ over Thailand; Insight towards the Solution for Air Pollution and Climate Change - Vanisa Surapipith; Kasemsan Manomaiphiboon; Narisara Thongboonchoo; Viphada Boonlerd; James H. Crawford; Myatthu Kyaw (My University, 2026)
The intensive Airborne and Satellite Investigation of Asian Air Quality (ASIA-AQ) mission has been the NASA led international cooperative field study designed to address local air quality challenges in Asia. Specifically, ASIA-AQ flight observations over Bangkok and its vicinity (BKV) during March 2024 suggest the presence of daytime pollution and heat islands for which aerosol and certain gaseous constituents intensify over the urban core and so does temperature. Asymmetry of their spatial patterns is potentially linked to diverse land cover (also human activities) and more importantly the land-sea interface where internal boundary layers (both thermal and mechanical) develop. The DC-8 flight monitored aerosol (backscatter), O3, NO2, and CO concentrations, that were used to identify the extent of daytime pollutant island. Spatial distribution of pollutants and temperature in BKV and human exposure are illustrated by integrating with population distribution and urban structure. The findings indicate public health situation and projection of inhabitants. This study allows insight towards solutions for Air Pollution and Climate Change Impacts for redesigning and resilience planning for Urban Ecosystem in Thailand. Communications to policy makers are also demonstrated so that achieving the SDG meets the Net-Zero commitment of Bangkok Metropolitan Administration, while public attention is high in many forums across the capital city.
Keywords: Urban Heat Island Mitigation; Science and Climate Studies; COVID-19 impact on air quality